Improved antibody breadth with an extended primary dose interval of COVID-19 vaccine is overcome by boosters - Ahmed, Jessica I.; Krosta, Samantha J.; Reimer, Mandy N.; Cheung, Winnie; Mesa, Christine; Lopez, Carmen; Chua, Rayeil J.; Alsattari, Farah; Robinson, Alyssia; Manguiat, Kathy; Jahan, Naima; Abrenica, Bernard; et al. (Frontiers in Immunology, 2025)
IntroductionDuring rollout of mRNA-based COVID-19 vaccines, several jurisdictions extended the interval between the first and second doses to prioritize wider population access to limited vaccine supply. This study evaluated the effects of an extended dose interval on development of antibody and cell-mediated responses following the primary dose series and a subsequent booster dose.MethodsBlood samples were collected from mRNA COVID-19 vaccine recipients at baseline and longitudinally after each dose. Samples were analyzed for SARS-CoV-2-specific antibody titers, neutralizing antibodies and memory T cell responses.ResultsAn extended dose interval was associated with improved breadth of neutralizing antibody responses against both ancestral and early SARS-CoV-2 variants, but not Omicron variants. Dose interval had no impact on the development of antigen-specific memory T cell responses, the memory or T helper phenotypes of responding T cells or cytokine production. The effects of the primary dose interval on immune outcomes were no longer evident after a third dose of mRNA vaccine.DiscussionAn extended primary dose interval resulted in short-term benefits to humoral immunity but these were transient in the context of subsequent exposures. However, in addition to the public health benefits of wider population access to vaccines, the short-term immunological benefits of extending the dose interval may have been sustained in the absence of boosters. These findings underscore the importance of evaluating dosing intervals during the development of future vaccine candidates.